2015
DOI: 10.1155/2015/534690
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Primary School Teacher and Student Attitudes towards Science and Technology

Abstract: This study focuses on the effects of teachers’ attitudes towards teaching about science and technology on student attitudes towards science and technology. A one-year longitudinal study involving 91 teachers and 1822 students from the higher years of Dutch primary schools showed that students develop less positive attitudes towards science and technology during their primary school years and that girls showed less positive attitudes than boys. Female teachers showed less positive attitudes towards teaching abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 23 publications
1
32
1
18
Order By: Relevance
“…Gender didn't have any significant influence in both treatment and control students' attitudes towards science, differing from the tendency showed in previous studies (i.e. Denessen et al 2015;DeWitt & Archer, 2015;De Pro Bueno & Pérez Manzano, 2014;Jarvis & Pell, 2005), but being similar to those obtained by Akpinar et al (2009). Overall, these results seem to indicate that the model proposedusing a coupled inquiry and clearly defining each of the phases needed for integrating the different STEM subjects -may be useful for the design of other STEMs teaching units for the elementary level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Gender didn't have any significant influence in both treatment and control students' attitudes towards science, differing from the tendency showed in previous studies (i.e. Denessen et al 2015;DeWitt & Archer, 2015;De Pro Bueno & Pérez Manzano, 2014;Jarvis & Pell, 2005), but being similar to those obtained by Akpinar et al (2009). Overall, these results seem to indicate that the model proposedusing a coupled inquiry and clearly defining each of the phases needed for integrating the different STEM subjects -may be useful for the design of other STEMs teaching units for the elementary level.…”
Section: Discussioncontrasting
confidence: 99%
“…Research into elementary students' attitudes toward science confirmed that girls tend to report more unfavourable attitudes than boys. More specifically, girls enjoy less science lessons (Denessen, Vos, Hasselman, & Louws, 2015) and boys have more aspiration in science than girls (DeWitt & Archer, 2015). Also, it seems that as grade level increase, favourable attitudes toward science decrease drastically (Ali et al, 2013;Said, Summers, Abd-El-Khalick, & Wang, 2016).…”
Section: Attitudes Toward Sciencementioning
confidence: 99%
“…However, students develop their views of science when they are young, and by age 14 their attitude toward science is confirmed and will have an effect on their future career choice (Denessen, Vos, Hasselman, & Louws, 2015). As a consequence, more recent research has focused on primary science with research on attitudes extending to the primary school (Silver & Rushton, 2008).…”
Section: Attitude Studies Internationally and In New Zealandmentioning
confidence: 99%
“…Others note how student attitudes become less positive over time. Denessen et al (2015) posited that students develop less positive attitudes toward science during their primary schooling. A similar trend has been noted in New Zealand.…”
Section: Attitude Studies Internationally and In New Zealandmentioning
confidence: 99%
See 1 more Smart Citation